2007
DOI: 10.1556/aagr.55.2007.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1-MCP treatment on apple biochemical content and physiological disorders

Abstract: The research was conducted with the apple ( Malus domestica ) cultivars Krameri Tuviõun and Talvenauding at the Estonian Agricultural University during 2003–2005. The aim was to study the effect of 1-methylcyclopropene (1-MCP) treatment (1 ppm, at room temperature, 24 h) on the biochemical content and physiological disorders of apples and on external quality after 4 months of storage. The apples were stored in a normal atmosphere at 2–5°C and 80–85% RH. In the first storage season 1-MCP treatment did not imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
1
5
0
2
Order By: Relevance
“…Though, it should be mentioned that the most significant degradation of vitamin C was observed for 1-MCP-treated fruit (research year 2012-2013), while in 2013-2014 for fruit kept under cold storage conditions. Similar observations were reported by Moor et al (2007), who pointed out that the 1-MCP influence might be yeardependent where the key driver is average air temperature during vegetation period which greatly influences fruit maturity. Moreover, different fruits display different absorption rate of 1-MCP, which may be attributed to the insoluble dry matter, or due to spatial variation in binding (Nanthachai et al, 2007).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Though, it should be mentioned that the most significant degradation of vitamin C was observed for 1-MCP-treated fruit (research year 2012-2013), while in 2013-2014 for fruit kept under cold storage conditions. Similar observations were reported by Moor et al (2007), who pointed out that the 1-MCP influence might be yeardependent where the key driver is average air temperature during vegetation period which greatly influences fruit maturity. Moreover, different fruits display different absorption rate of 1-MCP, which may be attributed to the insoluble dry matter, or due to spatial variation in binding (Nanthachai et al, 2007).…”
Section: Resultssupporting
confidence: 86%
“…Moreover, different fruits display different absorption rate of 1-MCP, which may be attributed to the insoluble dry matter, or due to spatial variation in binding (Nanthachai et al, 2007). In the first year of research, the decrease in vitamin C indicated that 1-MCP treatment might even facilitate fruit ripening, while in the second year 1-MCP-treated apple were contained more vitamin C than control samples (Moor et al, 2007). In terms of 0.85 -ULO storage, it was found that degradation of vitamin C appears both aerobic and anaerobic pathways (Mercali et al, 2014), thus explaining why such decline in vitamin C occurs in this type of storage.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the AA content was better retained in 1-MCP-treated apples (cv. Talvenauding) in one experimental year, but not in a second year [97], suggesting that the impact of preharvest factors or harvest maturity on AA content might have a greater influence than any effects on the ethylene inhibitor.…”
Section: Postharvest Technologies and Their Impact On Quality And Phymentioning
confidence: 88%
“…Moreover, McArtney et al (2011) reported a significant effect of 1-MCP treatments in terms of reduction of rots caused by phytopathogenic fungi on apple fruits. Also, apple fruit quality was improved by 1-MCP because treated fruits contained more vitamin C, the loss of titrable acids was delayed, soluble solid content (SSC) decreased, and fruit rot consequently decreased 30% (Moor et al 2007). Li et al (2017) found that 1-MCP treatment enhances the oxidative damage of spores and mycelia of P. expansum and destroys the integrity of plasma membrane of spores, and thus inhibits blue mold on apple fruits.…”
Section: Discussionmentioning
confidence: 99%